Interaction Between Low Molecular Weight Dextran Sulphate and Bentonite adsorbed Plasma - Matsuda, T.; Ogawara, M.; Seki, T.; Miura, R.; Yokouchi, M.; Murakami, M. (Thrombosis and Haemostasis, 1979)
Effects of low molecular weight dextran sulphate (D.S.; mean molecular weight = 6,0006,500; S content = 17-19%) and/or bentonite (Wako Pure Chemical Industries, Osaka, Japan) adsorbed plasma (supernatant from plasma mixed with 300 mg/ml of bentonite for 10 minutes at 37°C), which contains no fibrinogen nor antithrombin III but α2 macro-globulin, α1-antitrypsin and α2-plasmin inhibitor, on thrombin time or batroxobin (purified fraction of venom of Bothrops atrox) time of fibrinogen solution were investigated. Addition of D.S. or bentonite adsorbed plasma to fibrinogen solution resulted in prolongations of thrombin time and batroxobin time. These results indicate that both D.S. and bentonite adsorbed plasma inhibit conversion of fibrinogen to fibrin by thrombin or batroxobin. However, when appropriately diluted bentonite adsorbed plasma and D.S. were added to fibrinogen solution simultaneously, thrombin times and batroxobin times were shorter compared to those when either bentonite adsorbed plasma or D.S. but not both was added. From these results, it is concluded that D.S. and bentonite adsorbed plasma interact to inhibit each other.